Microbiome in Reflux Disorders and Esophageal Adenocarcinoma - Yang, Liying (2014)
The incidence of esophageal adenocarcinoma has increased dramatically in the United States and Europe since the 1970s without apparent cause. Although specific host factors can affect risk of disease, such a rapid increase in incidence must be predominantly environmental. In the stomach, infection with Helicobacter pylori has been linked to chronic atrophic gastritis, an inflammatory precursor of gastric adenocarcinoma. However, the role of H. pylori in the development of esophageal adenocarcinoma is not well established. Meanwhile, several studies have established that a complex microbiome in the distal esophagus might play a more direct role. Transformation of the microbiome in precursor states to esophageal adenocarcinoma—reflux esophagitis and Barrett’s metaplasia—from a predominance of gram-positive bacteria to mostly gram-negative bacteria raises the possibility that dysbiosis is contributing to pathogenesis. However, knowledge of the microbiome in esophageal adenocarcinoma itself is lacking. Microbiome studies open a new avenue to the understanding of the etiology and pathogenesis of reflux disorders.